Forms and Methods of Supply Chain Management of the Oil Industry in the 1920-ies. Activity of Oil Industry Council - Elena V. Bodrova; Valery I. Elinski; Viacheslav V. Kalinov (International Journal of Supply Chain Management, 2019)
On the basis of archival materials first introduced into scientific circulation, they studied the problem of the oil industry evolution in the 1920-ies, the specifics of the forms and methods of party-state management. The results of the activity and the role of the most prominent specialists who were the members of the Petroleum Industry Council at that time based on the supply chain management. During this period, the oil industry had great centralization of management, private capital was almost not allowed, self-financing was implemented to a minimum. Only oil trusts were to transfer all products to the industry syndicate. At the same time, archival documents allow not only to evaluate the colossal efforts of experts to restore and re-equip the industry, but also its importance for the development of the entire national economy in the context of the new economic policy implementation, make it possible to formulate the conclusion that by the end of the 1920-ies own research and development for the oil industry has become a fairly voluminous list.